1995
DOI: 10.1104/pp.108.1.141
|View full text |Cite
|
Sign up to set email alerts
|

Three Glycosylated Polypeptides Secreted by Several Embryogenic Cell Cultures of Pine Show Highly Specific Serological Affinity to Antibodies Directed against the Wheat Germin Apoprotein Monomer

Abstract: Embryogenic tissues of Pinus caribaea Morelet var hondurensis produce extracellular proteins; among them germins have been identified. Two-dimensional electrophoresis followed by electroblotting onto a polyvinylidene difluoride membrane allowed isolation and N-terminal amino acid sequencing of extracellular CP111, which is present within the five embryogenic cell lines studied. l h e amino acid sequence showed strong homologies with the sequences of germins deduced from cDNA sequencing, starting at the same am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 21 publications
2
38
1
Order By: Relevance
“…Domon et al [57] compared profiles of secreted proteins, which were detected on the surface of preglobulary somatic embryos of four embryogenic cell lines of Pinus caribaea and those, on the contrary to our results, were very similar. This study was based on literature presenting the hypothesis that chitinases are potential markers for embryogenesis, confirmed by differences in extracellular protein profiles among embryogenic cell lines with different embryogenic capacity [17,58] and also between embryogenic and nonembryogenic cell lines [18,[23][24][25]57,[59][60][61]. However, our results showed that in the 18 embryogenic cell lines of P. nigra and the seven cell lines of hybrid firs tested, the presence or absence of any one detected isoform cannot be distinctly associated with the high or low embryogenic potential of the tested cell lines.…”
Section: Discussioncontrasting
confidence: 97%
“…Domon et al [57] compared profiles of secreted proteins, which were detected on the surface of preglobulary somatic embryos of four embryogenic cell lines of Pinus caribaea and those, on the contrary to our results, were very similar. This study was based on literature presenting the hypothesis that chitinases are potential markers for embryogenesis, confirmed by differences in extracellular protein profiles among embryogenic cell lines with different embryogenic capacity [17,58] and also between embryogenic and nonembryogenic cell lines [18,[23][24][25]57,[59][60][61]. However, our results showed that in the 18 embryogenic cell lines of P. nigra and the seven cell lines of hybrid firs tested, the presence or absence of any one detected isoform cannot be distinctly associated with the high or low embryogenic potential of the tested cell lines.…”
Section: Discussioncontrasting
confidence: 97%
“…However, it is known that GLPs are glycosylated (33). All GLPs, including nectarin I, contain a conserved site of Nglycosylation (2,10,11,16,17,19,33). PAS staining (28) demonstrated the presence of carbohydrate on the purified nectarin I protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Germin was first detected in germinating cereals, but subsequently, germin-like proteins were also identified in a protist (Lane, 1991), dicotyledonous angiosperms (Delseny et al, 1994;Heintzen et al, 1994), and gymnosperms (Domon et al, 1995). Germins and germin-like proteins constitute a large family of proteins ubiquitously distributed in the plant kingdom.…”
Section: Introductionmentioning
confidence: 99%